The State of Labor Discipline in the Urals Mining Industry in the Late 19th-Early 20th Century - Korobkov, Yuriy; Filatov, Vladimir; Krivonogova, Svetlana; Tomarov, Aleksey; Velikanova, Svetlana; Chernykh, Oksana (Journal of History Culture and Art Research, 2018)
There is a steady research interest in modern Russian social science in studying the characteristics of the labor behavior of modern Russian workers, primarily in terms of revealing the degree of its adequacy to social and economic reforms. At the same time, the problem of the reverse influence of labor moral on the direction and character of transformations is investigated far less. The solution of these problems involves their consideration in a broader historical perspective. This circumstance and the insufficient study of this problem at the regional level of the post-reform Urals caused the choice of the topic. In the course of the study, conclusions were drawn about the low quality of the production discipline of the mining and metallurgical workers of the Urals. Its typical features throughout a long historical period were absenteeism, tardiness, drunkenness, theft of factory property, non-observance of safety measures. This practice took the most widespread character during the revolutions of the beginning of the XX century.